Study on Mechanical Properties and Optimum Fiber Content for Basalt/Polyacrylonitrile Hybrid Fiber Reinforced Concrete - Zhenhai Zeng; Chuanxi Li; Zhuoyi Chen; Lu Ke (Advances in Materials Science and Engineering)
In order to obtain the design method of hybrid fiber reinforced concrete with better mechanical properties, the hybrid effect of fiber and the optimal fiber dosage are studied. In this paper, basalt fiber (B fiber) and polyacrylonitrile fiber (P fiber) were adopted. The mechanical properties such as compressive strength, splitting tensile strength, and bending toughness of concrete specimens with different fiber volumes were tested. The compressive strength, compressive modulus of elasticity, tensile strength, flexural capacity, and bending stress-strain curves of concrete with different fiber volumes were obtained, and the coefficient of hybrid effect and the ratio of toughness were calculated accordingly. The results show that the addition of fiber has little effect on the compressive modulus of elasticity of concrete, and the tensile strength, flexural strength, and toughness ratio are significantly increased, but the compressive strength is slightly decreased. The mechanical properties of hybrid fiber reinforced concrete, such as compressive strength, tensile strength, flexural strength, and toughness ratio, are better than those of single fiber reinforced concrete. The analysis of the fiber hybrid effect coefficient shows that there is a good hybrid effect between the two types of fibers. When the volume contents of B fiber and P fiber are, respectively, 0.15% and 0.11%, the comprehensive mechanical property of fiber reinforced concrete is the best. Meanwhile, the mechanical properties of the early-age concrete (3 d and 7 d) with this admixture are better than those of the plain concrete.